Effect of surface roughness on the interface behavior of clayey soils - Kadhim Hala K.; Alyounis Mohamad (Open Engineering, 2024)
This study investigates the effect of surface roughness on the interface behavior between clayey soils and structural materials, aiming to determine the necessary parameters for soil-structural interaction. The research site, located in one of Iraq’s seismically active regions, was selected for its significance. Experimental measurements were conducted using the SRT-6210 Digital Surface Roughness Tester to assess the roughness characteristics of steel and concrete samples. Four distinct roughness parameters were measured, and their correlation with shear parameters was analyzed. The shear behavior of clay-steel and clay-concrete interfaces was successfully described using the average roughness parameter (Ra), which exhibited the strongest correlation with shear parameters. Direct shear box and interface shear box tests were employed to identify soil’s shear strength parameters and evaluate interface shear strength parameters. The experimental findings highlight the significant influence of surface roughness on the shear strength parameters of clay-steel and clay-concrete interfaces. The interface shear strength, friction angle, and adhesion exhibited an increasing trend with roughness. Notably, shear strength increased by approximately 29.76% when concrete sample roughness was below 20 μm and by 32.8% when steel sample roughness was below 30 μm. Moreover, increasing surface roughness improved the interface friction angle of clay-steel and clay-concrete samples by about 37.95 and 36.3%, respectively. Additionally, an increase in roughness led to a rise in the adhesion of concrete and steel samples by approximately 26.24 and 32%, respectively. These findings emphasize the significance of surface roughness in optimizing the interface behavior between clayey soils and structural materials. The results have important implications for enhancing the design and performance of soil-structural systems.